Early Estimation of NFRs for Embedded System Using Design Metrics - Vieira, Andrws; Faustini, Pedro; Carro, Luigi; Cota, Érika (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2014)
In this paper, an approach is proposed to assist the designer in evaluating the impact of a design choice with respect to the Non-Functional Requirements (NFRs) in embedded systems. We use design metrics extracted from class diagrams and regression models to estimate, in the early development stages, the impact of software changes on NFRs. This prediction can be used during the first design to compare alternative design changes before implementation. Such an early estimation allows an efficient design space exploration with no penalty in the development time, which are crucial aspects for an embedded system.